Análise fundiária e ambiental do portal terra da saudade no município de Matão – SP à luz da desconstrução espacial - Cardoso, Jesse Romero (2015)
The analysis of spatial transformations passing a priori by deconstructing something. Despite the negative prefix deconstruction is far from a bad thing, above all, it is needed. Deconstruction varies from minimum to maximum, it is up to man the responsibility to lead it minimally so that does not cause negative impacts on the natural environment, this, condition to meet the "needs" of future generations. Deconstruction happens by working in geographic space, where everything is produced is space. Undoubtedly, we are products of ourselves, just as we are products of space, this space where man is present. The need for space becomes paramount when it comes to housing. In the municipality of Matão -SP , the heart of our research , according to the Local Plan for affordable housing , there is a housing deficit of 1,700 homes. To try to remedy this deficit the Municipality deployed in the northern area of the city Portal Terra da Saudade. This set of social housing came to contemplate 761 families, with 658 units of the program Minha Casa, Minha Vida, and 103 units of FNHIS, the project was a big step in that it aims to meet housing demand for the low population income of up to two minimum salaries. This study analyzed the social viability, focusing on the issue of land tenure, urban planning and law regulating the area for the Portal and the impacts to the environment, especially the APP (Permanent Preservation Areas), in the light of the spatial deconstruction. We highlight the impacts to APP , the disappearance of a spring in the Portal , as well as an effluent dump untreated into two streams in the area studied . We detected some mistakes in the documents that made possible the acquisition of the area to implement the housing project .